But If It’s Not Music, What Is It? Defining Interstitial Artistic Practices - Canonne, Clément; Fryberger, Annelies (Circuit, 2020)
We often think of art as structured in art worlds. But what lies between art worlds? Do we find spaces of undefined practices, or are interstitial practices also clearly defined? For this text, we interviewed 11 French artists with sound-based practices who situate themselves in the spaces where music overlaps with the visual arts, instrument building, performance art, and poetry. How do these artists define themselves, given that the available labels do not satisfy them? How do they actually use established categories when they do not want to make their artistic practice conform to them? Three positioning strategies came up recurrently in our interviews: so-called negative, additive, and generic definitional strategies. We show here that each of these definitional strategies implies related artistic choices, which make it possible for these artists to both legitimize their sense of belonging to an interstitial space and to use this belonging as a powerful means to develop a unique identity. Beyond a simple, sometimes superficial, refusal to be labeled, the strategies we identify appear to be the true markers of “interstitial” artists and their careers within and around art worlds.